The effects of social media opinion leaders’ recommendations on followers’ intention to buy - Huhn, Renata; Ferreira, Jorge Brantes; Freitas, Angilberto Sabino de; Leão, Fernanda (Review of Business Management, 2017)
Purpose – The objective of this study is to investigate how consumers are influenced in their intention to buy after having access – within social media – to persuasive messages sent out by digital opinion leaders. Design/methodology/approach – Data collection carried out via survey and data analysis carried out with the use of structural equation modeling. Findings – Digital opinion leaders capable of generating persuasive messages can change the attitudes of followers and make them accept the information provided, influencing their intention to buy evaluated products. Originality/value – The results show that it was possible to verify the direct and positive relationship between the persuasiveness of a message and the acceptance of the information contained in this message, while also indicating a significant relationship between the persuasiveness of the message and attitude change in relation to the purchase of goods evaluated by it. This highlights the relevance of these digital opinion leaders to the definition of marketing strategies by companies.